The Effectiveness of Cognitive-Behavioral Therapy on Emotional Processing and Selective Attention in Children with Learning Disabilities - Molaie, Rouhangiz (Mental Health and Lifestyle Journal, 2024)
This study aimed to examine the effectiveness of cognitive-behavioral therapy (CBT) on improving emotional processing and selective attention in children with learning disabilities. A randomized controlled trial was conducted with 30 children (aged 9–12) diagnosed with learning disabilities in Tehran, Iran. Participants were randomly assigned to an experimental group (CBT; n = 15) and a control group (n = 15). The CBT program consisted of ten 90-minute sessions implemented over five weeks. Standardized tools—the Emotional Processing Scale for Children (EPS-C) and the Stroop Color-Word Test (SCWT-C)—were used to assess the dependent variables at three time points: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests via SPSS version 27. The results revealed significant time × group interaction effects for both emotional processing (F(2, 56) = 18.59, p < .001, η² = .40) and selective attention (F(2, 56) = 15.78, p < .001, η² = .36). Post-hoc analysis indicated that the CBT group showed significant improvements in emotional processing from pre-test to post-test (MD = 10.16, p < .001) and to follow-up (MD = 11.22, p < .001), with similar significant gains in selective attention (pre-test to post-test: MD = -7.83, p < .001; to follow-up: MD = -7.24, p < .001). No significant changes were observed in the control group. The findings demonstrate that cognitive-behavioral therapy is an effective intervention for enhancing emotional regulation and selective attention in children with learning disabilities, with sustained effects observed over a five-month period. The study supports the integration of CBT-based programs into psychoeducational services for this population.